Changes in the Supply Duration of Combined Oral Contraception During the Coronavirus Disease 2019 (COVID-19) Pandemic. Issue 3 (March 2022) - Steenland, Maria W.; Rodriguez, Maria I.; Cohen, Jessica L.
Abstract : The duration of oral contraception supplied at first prescription pick-up increased modestly during the coronavirus disease 2019 (COVID-19) pandemic, but the pandemic did not dramatically alter combined oral contraceptive supply–prescribing practices.